What are They Saying About Your Head Coach? The Relationship Among Political Skill, Reputation, and Effectiveness - Minjung Kim; Janelle E. Wells; Amy Chan Hyung Kim (Journal of Applied Sports Management, 2016)
Influential leaders in competitive sport fields effectively use political skill to enhance their reputation, gain followers, and obtain support from organizations. In this study, a structural model was tested to determine the mediating role of leader reputation in the relationship between leader political skill and leader effectiveness. A total of 248 NCAA Division I assistant coaches were recruited for participation in a survey on their head coaches’ political skill, reputation, and perceived team-unit and leader-unit effectiveness. The results supported an indirect effect of head coaches’ reputation on their political skill and effectiveness, rather than a direct effect of political skill on leader effectiveness. On this basis, it was concluded that the strong and positive reputation that politically skilled head coaches build facilitates leader effectiveness in collegiate sports.
Keywords: political skill; leader reputation; leader effectiveness; intercollegiate sports